Serum cytokeratin-18 fragments as quantitative markers of epithelial apoptosis in liver and intestinal graft-versus-host disease - Luft, Thomas; Conzelmann, Michael; Benner, Axel; Rieger, Michael; Hess, Michael; Strohhaecker, Ulrich; Görner, Martin; Hegenbart, Ute; Ho, Anthony Dick; Dreger, Peter (Blood, 2007)
Graft-versus-host disease (GVHD) is the main complication of allogeneic stem cell transplantation. However, diagnosis of GVHD and evaluation of response to immunosuppressive treatment is sometimes difficult. Since apoptosis is the histopathologic hallmark in GVHD, we investigated whether active GVHD-induced target organ destruction is mirrored by serum levels of the caspase-cleaved neo-epitope of cytokeratin-18 fragments (CK18Fs). Serum CK18F kinetics was monitored by M30 antibody-based enzyme-linked immunosorbent assay (ELISA) in 50 patients who fulfilled histopathologic and/or clinical criteria diagnostic for GVHD. Both intestinal and hepatic GVHD were consistently associated with significant elevations of CK18F levels over baseline. Responses of GVHD to immunosuppressive therapy were paralleled by CK18F decreases, whereas resistant GVHD was characterized by persistent CK18F rises. Clinical conditions that might represent relevant differential diagnoses, such as toxic mucositis, noncomplicated, infection-related diarrhea, and veno-occlusive disease were not associated with CK18F elevations. In conclusion, CK18F monitoring provides a serum marker for quantitative assessment of GVHD-associated apoptotic activity in intestinal and hepatic GVHD. Although apoptosis is not GVHD-specific, CK18Fs may help to distinguish active GVHD from GVHD-unrelated conditions with similar symptoms, and to monitor response to immunosuppressive treatment. Prospective studies are warranted to evaluate how CK18Fs may assist in the diagnosis, grading, and treatment guidance of GVHD.